Relationship between Retinal Nerve Fiber Layer with Visual Field Defect in Non Proliferative Diabetic Retinopathy - Alfurqon Alfurqon; Ramzi Amin; AK Ansyori (Majalah Oftalmologi Indonesia, 2015)
Background: In the early stages of diabetic retinopathy, neuronal abnormalities include changes in ganglion cell death. Neuronal apoptosis is suspected as one of the causes responsible for the occurrence of lesions at an early stage of diabetic retinopathy, which results in a decrease in number of ganglion cells and thinning of the layer of ganglion cells, which can be caused by several mechanisms including glutamat excitoxicitate, oxidatice stress, hyperglichemia, and neuroinflamation. Retinal ganglion cell death and axonal degeneration, will cause thinning of the retinal nerve fiber layer (RNFL) which may result in a decrease in neural function, which in turn have an impact on the occurrence of visual field defects. This study is to determine the relationship between the thickness of RNFL with visual field defects in patients with non-proliferative diabetic retinopathy (NPDR). Methods: This study is a comparative analytic cross-sectional design with sample of 66 eyes of 34 people in clinic of retina subdivision of Moh. Hoesin Hospital Palembang from July to November 2013. Patients of NPDR examined fundus photo, Oculo Coherence Tomograph and Humphrey Field analyzer. Results: RNFL thickness average in this study is 104.4Â±10.9 Î¼m. Visual field defect occur ini moderate and severe NPDR. Conclusion: There is a strong relationship between RNFL thickness with visual field defects in patients NPDR (r =-0.693). Keywords: RNFL thickness, visual field defect, NPDR Â